The Influence of Promotion Strategies on the Sales Level of Food Products at Kedai JAM - Sindi; Abidin, Zaenal; Kuswanto; Ikhlas, Muhammad (CV. Zabags Qu Publish, 2025)
In the face of increasing digital competition, micro, small, and medium enterprises (MSMEs) are required to adapt by implementing technology-based promotional strategies to strengthen their market presence and boost sales performance. This study aims to examine the influence of digital promotional strategies on the sales of food products at Kedai JAM, an MSME located in Muara Sabak Timur, Jambi. Utilizing a quantitative approach with a causal research design, primary data were collected through questionnaires from 90 consumers who had been exposed to the business’s promotional content on Facebook. The instrument measured key dimensions of promotional strategy namely attractiveness, promotional media, consistency, and creativity while sales performance was evaluated based on sales volume, revenue, purchase frequency, and new customer acquisition. The results of the regression equation obtained were Y = 6.604 + 0.880X, with a significance value of 0.000 and thitung 12.243 > ttabel 1.662, which means that there is a significant influence of promotional strategies on sales levels. A determination coefficient (R²) value of 0.630 indicates that 63% of sales variations were influenced by promotional strategies, while 37% were influenced by other factors outside the study. These findings suggest that Facebook functions not only as an efficient promotional medium but also as a strategic marketing platform capable of influencing consumer behavior and expanding market reach. This study offers practical insights for MSME promotion strategies and contributes to the theoretical discourse on digital marketing within the context of community-based entrepreneurship.